Analisis Sistem Dinamis pada Produksi Pabrik Tahu di Kota Cilegon - Ainurroffi, Roy; Fidianto, Ade Age; Hibatullah, Fajar; Firmansyah, Muharrom; Sahrupi, Sahrupi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This article presents the findings of a study on the analysis of the dinamis system in tahu production in Cilegon, Indonesia, with an emphasis on the importance of small and medium-sized businesses (UKM) in the food industry.The primary goal of this research is to understand the factors that affect production efficiency, product quality, and keberlanjutan in the tahu industry. The methodology used in this study involves gathering data through silent observation, observation of industrial activities, and relevant literature reviews. Based on the collected data, the researcher created a causal loop diagram (CLD), which illustrates the complex relationship between the variables, such as the price of goods, market demand, and production process supply